Assessment of own life prospects as a factor of student’s academic motivation - Serdiuk, Liudmyla (Social Welfare: Interdisciplinary Approach, 2013)
The paper analyzes life perspective indexes and life purpose orientations of sample students enrolled into an integrated learning environment. A comparative analysis of the data on students with disabilities and healthy students was performed. Characteristics of interrelation between value and life purpose orientation indexes and students’ academic motivation were researched. Dual determination of human behavior by temporal factors was stated: the frst type defnes behavior regulation within a short period of time, in specifc situations, activities, and the second one determines behavior regulation for a long time and is associated with planning of well-aimed self-development.